ANALISIS TEMUAN BERULANG PADA PEMERIKSAAN BANTUAN KEUANGAN DEWAN PIMPINAN DAERAH PARTAI POLITIK PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Rahayu Alkam (Master in Accounting Program, 2019)
ABSTRACT This research was to analyze the causes of the repeated findings and their preventive solutions in the audit of the public funding of the Regional Representative Council (DPD) of the political parties in the Province of Yogyakarta Special Region. It was a qualitative research with a case study design conducted in four DPDs receiving the largest public funding from 2011 to 2016. Data were collected through document analyses and interviews. Twelve participants interviewed were the representatives of three parties, namely compilers, examiners, and users of the public funding audit system.This research also applied the Committee of Sponsoring Organizations of the Treadway Commission (COSO) internal control framework and the State Financial Audit Standards (SPKN) of 2017 for the analysis. The analysis showed three causes of repeated findings in the audit; they were weak internal control of political parties, weak audit, and non optimal role of the National Unity and Political Body. Preventive solutions to be made are for improving internal control, improving regulations, and optimizing coordination among parties. The results indicate that improvements should not be done only within the internal political parties but also around the external factors.